Indonesia and the WTO Dispute Settlement System - Joseph Wira Koesnaidi; Junianto James Losari (Journal of World Trade Studies, 2010)
This paper discusses several issues in relations with Indonesia and its utilization of the WTO Dispute Settlement System as a Complainant or a Third Party. It is shown that Indonesia has not yet active using the WTO Dispute Settlement System to secure its trading rights under the WTO. Therefore, optimism on the future of Indonesia and WTO Dispute Settlement System should be built since the government sees the importance of WTO litigations for our national interests and due to the WTO is a rule-based system and its major achievement is to have an effective dispute settlement mechanism.